Evaluasi Tata Letak Fasilitas Pabrik untuk Meningkatkan Efisiensi Kinerja Menggunakan Metode SLP (Systematic Layout Planning): Studi Kasus PT. XYZ - Nida An Khofiyah; Muhammmad Rizki; Balazi Gea; Tri Ngudi Wiyatno; Supriyati (Universitas Islam Raden Rahmat, Malang, 2023)
The layout of factory facilities is one of the things that must be evaluated along with technological developments, increasing demand and the need for production which is increasing so that performance efficiency can be achieved. PT XYZ is a company engaged in the field of packaging with requests for tens of tons per day, this results in the need for a large factory area and the arrangement of facilities must be adjusted to the sequence of operations from raw materials to finished goods so that it will speed up the work process and be more efficient in movement of goods. On the other hand, the problem that arises is that all material handling work and WIP material handling (work in process) are carried out by several workers, so it is necessary to study the effectiveness and speed of the material handling process carried out in the production process at the company. For this reason, it is necessary to evaluate the layout of the facility to minimize material handling costs. The method used in research to fix this layout problem is the Systematic Layout Planning (SLP) method. Improving the layout of this company can also increase the efficiency and productivity of workers so that the time needed to carry out production is shorter.